A twist in time : a novel - McElwain, Julie (McElwain, Julie. Kendra Donovan series., 2017)
When Kendra Donovan<U+2019>s plan to return to the 21st century fails, leaving her stranded in 1815, the Duke of Aldridge believes he knows the reason<U+2014>she must save his nephew, who has been accused of brutally murdering his ex-mistress. Former FBI agent Kendra Donovan<U+2019>s attempts to return to the twenty-first century have failed, leaving her stuck at Aldridge Castle in 1815. And her problems have just begun: in London, the Duke of Aldridge<U+2019>s nephew Alec<U+2014>Kendra<U+2019>s confidante and lover<U+2014>has come under suspicion for murdering his former mistress, Lady Dover, who was found viciously stabbed with a stiletto, her face carved up in a bizarre and brutal way. Lady Dover had plenty of secrets, and her past wasn<U+2019>t quite what she<U+2019>d made it out to be. Nor is it entirely in the past<U+2014>which becomes frighteningly clear when a crime lord emerges from London<U+2019>s seamy underbelly to threaten Alec. Joining forces with Bow Street Runner Sam Kelly, Kendra must navigate the treacherous nineteenth century while she picks through the strands of Lady Dover<U+2019>s life. As the noose tightens around Alec<U+2019>s neck, Kendra will do anything to save him, including following every twist and turn through London<U+2019>s glittering ballrooms, where deception is the norm<U+2014>and any attempt to uncover the truth will get someone killed.